Patógenos em sementes de Pinus spp. - ênfase em Lasiodiplodia sp. e Fusarium spp. - Maciel, Caciara Gonzatto (2016)
The genus Pinus is highlight in the forestry sector, especially in southern Brazil, by production of wood and cellulose. However, their seeds are vulnerable to attack by fungi causing diseases in nurseries. The present study aims to evaluate the physiological and sanitary quality of Pinus spp. seeds. from different origins; morphological and molecular identification of fungal species isolated from seeds of Pinus sp.; evaluate the pathogenic potential these fungi; and testing the efficacy of biocontrol agents for the treatment of seeds. For initial characterization of seed were evaluated germination and sanity tests. Four lots were utilized and samples were composed of 400 seeds for each test. The morphological characterization of the fungal isolates was accomplished based on specific keys to the genera Fusarium and Lasiodiplodia. For the molecular identification, ITS region and elongation factor, were sequenced. The pathogenicity test consists of the inoculation of the pine seeds by contact with a fungal culture of the pathogen, the substrate was sterilized sand, the test was kept in a growth room (25 ± 3 °C and photoperiod of 12 h) during 45 days. For biocontrol tests were used commercial products based on Trichoderma and Bacillus; and an isolated Bacillus themselves obtained from pine seeds. The in vitro control was conducted by direct confrontation betweem antagonist and pathogen. The in vivo test was carried out in conditions of vegetation for 60 days, the variables evaluated were emergence, stem diameter, fresh weight and dry seedling. The germination percentage of lots was higher 70%. The fungal genera associated with seeds were: Fusarium, Lasiodiplodia, Aspergillus, Penicillium and Trichoderma. Based on morphological and molecular characteristics identified the species F. oxysporum, F. verticillioides and Lasiodiplodia theobromae as pathogenic species to Pinus spp., causing pre and post-emergence damping-off. The antagonists show control potential of F. oxysporum, F. verticillioides and Lasiodiplodia theobromae in vitro. In vivo tests does not interfere with the development of the seedlings, until the 60 days of test.